Sierra Six [large type] - Greaney, Mark (Greaney, Mark. Gray Man novel, 2022)
"Before he was the Gray Man, Court Gentry was Sierra Six, the junior member of a CIA action team. In their first mission, they took out a terrorist leader, at a terrible price. Years have passed. The Gray Man is on a simple mission when he sees a ghost: the long-dead terrorist, but he's remarkably energetic for a dead man. A decade of time hasn't changed the Gray Man. He isn't one to leave a job unfinished or a blood debt unpaid"--